Can Futures Market Data Be Used to Understand the Behavior of Real Interest Rates? - Mishkin, Frederic S (Journal of Finance, 1990)
This paper examines whether futures market data can be used to understand the behavior of real interest rates. Several ways of examining the data indicate that futures market data are not particularly informative about real interest rates. No only does this evidence cast some doubt on results in previous research that make use of futures market data to draw inferences about real interest rates, but it also indicates that future research on real interest rates may need to turn to a different line of attack.